The Becoming of the Complex Socium: New Causes of Deviance and Crime - Kravchenko, Sergey A. (International Journal of Criminology and Sociology, 2012)
This article focuses on the factors that influence the becoming of the complex socium. The author considers, in his opinion, the most characteristic parameters of the complex socium that is developing in the context of the ‘arrow of time’. He asserts that the becoming of the complex socium brings unintended consequences producing new causes of deviance and crime. Under these conditions he argues for the humanistic turn in sociology, based on non-linear and humanistic sociological imagination, and humanistic praxis.